2014
DOI: 10.3390/ijms15046224
|View full text |Cite
|
Sign up to set email alerts
|

Substance P Activates the Wnt Signal Transduction Pathway and Enhances the Differentiation of Mouse Preosteoblastic MC3T3-E1 Cells

Abstract: Recent experiments have explored the impact of Wnt/β-catenin signaling and Substance P (SP) on the regulation of osteogenesis. However, the molecular regulatory mechanisms of SP on the formation of osteoblasts is still unknown. In this study, we investigated the impact of SP on the differentiation of MC3T3-E1 cells. The osteogenic effect of SP was observed at different SP concentrations (ranging from 10−10 to 10−8 M). To unravel the underlying mechanism, the MC3T3-E1 cells were treated with SP after the pretre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 42 publications
(37 reference statements)
0
34
0
Order By: Relevance
“…We can only speculate that D3R could increase osteoblast differentiation by activating the Wnt/β-catenin signalling pathway, since we have only data regarding the D3R-induced upregulation of β-catenin mRNA and not β-catenin protein levels. This is a limitation of our study since it has been reported that the amount of βcatenin protein levels depends on the state of β-catenin destruction complex rather than the expression of β-catenin mRNA [46]. Considering the complexity of the Wnt/ β-catenin signalling pathway, further studies will be required to examine the effects of D3R on β-catenin protein levels both in the cytoplasm and in the nucleus and its ability to inactivate the destruction complex leading to GSK-3β phosphorylation and inactivation.…”
Section: Incubation Of Mc3t3-e1 Cells With T-bhp Induced a Significanmentioning
confidence: 89%
“…We can only speculate that D3R could increase osteoblast differentiation by activating the Wnt/β-catenin signalling pathway, since we have only data regarding the D3R-induced upregulation of β-catenin mRNA and not β-catenin protein levels. This is a limitation of our study since it has been reported that the amount of βcatenin protein levels depends on the state of β-catenin destruction complex rather than the expression of β-catenin mRNA [46]. Considering the complexity of the Wnt/ β-catenin signalling pathway, further studies will be required to examine the effects of D3R on β-catenin protein levels both in the cytoplasm and in the nucleus and its ability to inactivate the destruction complex leading to GSK-3β phosphorylation and inactivation.…”
Section: Incubation Of Mc3t3-e1 Cells With T-bhp Induced a Significanmentioning
confidence: 89%
“…The canonical Wnt pathway has been activated by SP in order to promote the proliferation and differentiation of BMSCs [ 16 , 34 , 35 ]. This current study illustrated the active canonical Wnt pathway could be induced by SP in the serum-deprived BMSCs.…”
Section: Discussionmentioning
confidence: 99%
“…Another study demonstrated SP's in vitro anabolic effect on mouse pre‐OB MC3T3‐E1 cell line whereby it upregulated the expressions of collagen type 1, ALP, Runx2 and osteocalcin at day 4. This effect was shown to involve the activation of Wnt/β‐catenin signalling pathway . Recently, Fu et al.…”
Section: Peptides From Nervous Systemmentioning
confidence: 99%
“…This effect was shown to involve the activation of Wnt/β-catenin signalling pathway. 218 Recently, Fu et al demonstrated that SP (10 −5 mM) promotes differentiation and migration capability of rat bone marrow MSCs and activates r AMSO, CORNISH, AND BRIMBLE BMP-2 expression in OBs. 219 The peptide also exerts an inhibitory effect on serum deprivationinduced apoptosis in bone marrow MSCs.…”
Section: B Substance Pmentioning
confidence: 99%